Gestão democrática e o provimento de cargos: a participação na escolha de gestores em escolas municipais de uma rede de ensino - Gonçalves, Mellany Canabarro (Universidade do Vale do Rio dos Sinos, 2025)
This work is the result of an academic research project submitted in partial fulfillment of the requirements for the Master’s Degree in Education at the Graduate Program in Education at Unisinos. It focuses on democratic management and the process of appointing school leadership positions in public schools, with an emphasis on community participation in this process. The theoretical framework is organized into four categories: Democracy, Democracy and Democratic Management in Education, Historical Materialism, and the Provision of the School Management Position and Democratic Management. The research was conducted in the municipal education system of São Leopoldo, in the state of Rio Grande do Sul, Brazil, seeking to understand how school leaders are selected and how democratic practices are manifested in everyday school life. A qualitative approach was adopted, combining the analysis of official documents regulating the selection of school leadership teams with interviews conducted with two school principals and two teachers. The results show that, although the municipality has regulations in place for the direct election of principals, there are still gaps between what is stated in the legislation and what occurs in practice. In some schools, the school community participates effectively in decision-making; in others, participation remains limited, particularly among families. Despite some progress — such as valuing open dialogue and the role of school councils — challenges persist, especially those related to time constraints, bureaucracy, and community engagement. The findings highlight the importance of strengthening practices that promote dialogue, shared responsibility, and the collective construction of school management, going beyond the electoral act and working toward the consolidation of a truly democratic culture in public education.
Keywords: Gestão democrática; Eleição de diretores; Participação; Escola pública; Provimento de cargos; Democratic management; Principal election; Participation; Public school; School leadership provision; ACCNPQ::Ciências Humanas::Educação